Maintaining the permanence principle for death during in situ normothermic regional perfusion for donation after circulatory death organ recovery: A United Kingdom and Canadian proposal. Issue 8 (27th January 2020) - Manara, Alex; Shemie, Sam D.; Large, Stephen; Healey, Andrew; Baker, Andrew; Badiwala, Mitesh; Berman, Marius; Butler, Andrew J.; Chaudhury, Prosanto; Dark, John; Forsythe, John; Freed, Darren H.; et al.
Abstract : There is international variability in the determination of death. Death in donation after circulatory death (DCD) can be defined by the permanent cessation of brain circulation. Post‐mortem interventions that restore brain perfusion should be prohibited as they invalidate the diagnosis of death. Retrieval teams should develop protocols that ensure the continued absence of brain perfusion during DCD organ recovery. In situ normothermic regional perfusion (NRP) or restarting the heart in the donor's body may interrupt the permanent cessation of brain perfusion because, theoretically, collateral circulations may restore it. We propose refinements to current protocols to monitor and exclude brain reperfusion during in situ NRP. In abdominal NRP, complete occlusion of the descending aorta prevents brain perfusion in most cases. Inserting a cannula in the ascending aorta identifies inadequate occlusion of the descending aorta or any collateral flow and diverts flow away from the brain. In thoracoabdominal NRP opening the aortic arch vessels to atmosphere allows collateral flow to be diverted away from the brain, maintaining the permanence standard for death and respecting the dead donor rule. We propose that these hypotheses are correct when using techniques that simultaneously occlude the descending aorta and open the aortic arch vessels to atmosphere. Abstract : The authors present techniques to prevent the restoration of brain perfusion during in situ normothermic regional perfusion by ensuring the diversion of any possible collateral supply.